Anchoring-driven spontaneous rotations in active gel droplets. Issue 35 (3rd August 2017) - Fialho, A. R.; Blow, M. L.; Marenduzzo, D.
Abstract : We characterise by computer simulations a new phenomenon involving spontaneous rotations in droplets of contractile and extensile active gels. Abstract : We study the dynamics of an active gel droplet with imposed orientational anchoring (normal or planar) at its surface. We find that if the activity is large enough droplets subject to strong anchoring spontaneously start to rotate, with the sense of rotation randomly selected by fluctuations. Contractile droplets rotate only for planar anchoring and extensile ones only for normal anchoring. This is because such a combination leads to a pair of stable elastic deformations which creates an active torque to power the rotation. Interestingly, under these conditions there is a conflict between the anchoring promoted thermodynamically and that favoured by activity. By tuning activity and anchoring strength, we find a wealth of qualitatively different droplet morphologies and spatiotemporal patterns, encompassing steady rotations, oscillations, and more irregular trajectories. The spontaneous rotations we observe are fundamentally different from previously reported instances of rotating defects in active fluids as they require the presence of strong enough anchoring and entail significant droplet shape deformations.